Simplify -5(.2k + 1) - 2(.4k -2)

1 answer

To simplify the expression -5(.2k + 1) - 2(.4k - 2), we will distribute the -5 and -2 through the parentheses and combine like terms.

-5(.2k + 1) = -1k - 5
-2(.4k - 2) = -0.8k + 4

So, combining the like terms -1k - 5 and -0.8k + 4, we get -1.8k - 1.
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions